Misappropriation of genetic resources and associated traditional knowledge: Challenges posed by intellectual property and genetic sequence information - Nirmalya Syam; Thamara Romero (South Centre, 2021)
Improper acquisition of genetic resources (GRs) and associated traditional knowledge (TK) without prior informed consent and on mutually agreed terms, in accordance with national laws of the country providing the GR and associated TK, as well as without any fair and equitable sharing of the benefits derived from their utilization, has been a significant concern for developing countries. Intellectual property (IP) rights can serve as one of the means of such misappropriation. One of the mechanisms sought by developing countries to prevent it consists in the establishment of an effective multilateral legal mechanism for defensive protection against misappropriation, primarily through the introduction of a mandatory disclosure requirement about the source and country of origin of such resources in intellectual property right (IPR) applications. These negotiations have been taking place in different fora. However, there is an increased sense of frustration due to the lack of progress in achieving consensus during the last twenty years. Meanwhile, new modes of misappropriation of GRs are evolving through the use of genetic sequence information and data of GRs, and by applying technological developments in synthetic biology. This paper discusses the use of IP and genetic sequence information and data as modes of misappropriation of GRs and associated TK and the deficits of the current international legal framework in preventing such misappropriation. This paper also maps the state of play of the ongoing negotiations in the context of these issues in different fora, and, in conclusion, proposes possible alternative approaches for addressing these pressing issues at the multilateral level.
Keywords: 300; Access and Benefit-Sharing (ABS); Convention on Biological Diversity (CBD); Disclosure; Food and Agriculture Organization (FAO); Free Trade Agreements (FTAs); Genetic Resources; Genetic Sequence Data (GSD); Genetic Sequence Information (GSI); Intellectual Property; Intellectual Property Rights (IPRs); International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA); Marine Genetic Resources; Misappropriation; Mutually Agreed Terms (MAT); Nagoya Protocol; Pandemic Influenza Preparedness (PIP) Framework; Patent; Prior Informed Consent (PIC); Synthetic Biology; Traditional Knowledge; TRIPS; United Nations Convention on the Law of the Sea (UNCLOS); UPOV Convention; World Health Organization (WHO); World Intellectual Property Organization (WIPO); World Trade Organization (WTO)